Poésie dans les bulles : la Divine Comédie de la terza rima aux fumetti - Sylvie Martin-Mercier (Perspectives Médiévales)
Based on three comic strip adaptations of the Divine Comedy, this article aims to highlight the variety of strategies for quoting the original text. It also analyses the effects produced by transcoding operations. By inserting Dante’s tercets into a new work, these processes, far from being a simple tribute to the source text, transform its graphic materiality. In this way, they make it resonate with a contemporary cultural object. A new meaning and a different relationship to the reader emerge.